Suitability of group-level oral fluid sampling in ruminant populations for lumpy skin disease virus detection - Dietze, K; Moritz, T; Alexandrov, T; Krstevski, K; Schlottau, K; Milovanovic, M; Hoffmann, D; Hoffmann, B (Elsevier BV, 2018)
The geographic expansion of Lumpy skin disease (LSD) from the near East into the European Union highlighted again the need for appropriate disease detection tools applicable to animal host populations where access to individual animals is difficult. This is of particular importance considering that the clinical manifestation of LSD is often mild making early disease detection challenging under the above-mentioned conditions. Building on positive experiences of group-level oral fluid sampling for pathogen detection as it is known to work for swine herds and wild boar, the concept was transferred to ruminants. Two groups of six cattle were infected experimentally with Lumpy skin disease virus (LSDV) under controlled conditions. Blood as well as oropharyngeal and nasal swab samples were collected at regular intervals. Group samples were obtained by placing cotton gauze around a salt lick block provided commonly as dietary supplement. Pieces of the gauze with visible signs of manipulation were tested in parallel to samples obtained from individual animals. Genome load analysis by qPCR technology revealed LSDV detection window starting from day 2 post infection until day 28 post infection, the end of the animal trial. At the individual level, detection periods varied between animals and type of sample and included intermitted detection. The accumulative character of the alternative sampling method makes it suitable to detect LSDV DNA at group-level even at times of the infection where a selective sampling of individuals from a group - as normally done in LSD surveillance - would have most likely failed in the detection.